Stroke Characteristics and Outcomes of Adult Patients in Northwest Ethiopia - Baye, Moges; Hintze, Amy; Gordon-Murer, Chloe; Mariscal, Tatiana; Belay, Gashaw Jember; Gebremariam, Aynishet Adane; Hughes, Charmayne M. L. (Frontiers in Neurology, 2020)
Stroke is becoming one of the leading causes of adult disability and death in sub-Saharan African countries. The aim of the present study is to provide an up-to-date account of the clinical and demographic characteristics of patients with stroke admitted to the University of Gondar College of Medicine and Health Science Comprehensive Specialized Hospital (CMHS). A hospital based retrospective study design was used to analyze the medical records of all patients with stroke admitted to CMHS from June 20th 2012 and April 30th 2018. Data were cleaned and entered into SPSS for analysis. Among the 448 patients with stroke admitted to CMHS, 58.0% (n = 260) of patients were female, and 42.0% (n = 188) were male. In the present sample, 141 (31.5%) had an ischemic stroke confirmed by neuroimaging, 82 (18.3%) had a hemorrhagic stroke confirmed by neuroimaging, and 252 (50.2%) had a stroke with undetermined type. The mean age of stroke was 63.9 years (range = 18-100, SD: 15.1 years), with no differences observed between stroke subtypes. The most common symptoms that led to patients seeking medical intervention were hemiparesis (67.4%), communication difficulties (56.0%), facial deviation (37.3%), and globalized headache (36.4%). Hypertension was the most commonly reported risk factor (37.1%), which was more prevalent in hemorrhagic (n = 37, 45.1%) than ischemic stroke patients (n = 53, 37.6%), stroke with undetermined type (n = 76, 33.8%). Stroke places a significant burden on sub-Saharan African countries. Results highlight the need to develop evidence-based public education programs, prevention programs that target individuals with risk factors, and methods to improve the clinical capacity to diagnose and treat individuals.